English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-10 12:38:05 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

f(a - 1) = -5(a - 1) - 1 = -5a + 5 - 1 = -5a + 4 .

2006-12-10 13:14:42 · answer #1 · answered by Anonymous · 0 0

Substitute a -1 wherever you see x.
So, f(a - 1) = -5(a - 1) - 1 = -5a + 5 - 1 = -5a + 4

2006-12-10 20:51:53 · answer #2 · answered by falzoon 7 · 0 0

f(a-1) = -5(a-1) -1

or (simplified)

f(a-1) = -5a + 4

2006-12-10 21:59:56 · answer #3 · answered by Jacob M 1 · 0 0

fedest.com, questions and answers